2019
DOI: 10.13005/bpj/1849
|View full text |Cite
|
Sign up to set email alerts
|

The Haematological Profiles of High Fat Diet Mice Model with Moringa oleifera Leaves Ethanol Extract Treatment

Abstract: Characteristics of obesity as dysfunction of adipose tissue and chronic low-grade inflammation can have impacts to haematological parameters. The Moringa oleifera leaves have been used empirically to treat metabolic and blood-related diseases. However, it is still unknown whether Moringa oleifera leaves can influence haematological parameters in high fat diet. The study aimed to investigate the hematological parameter of high-fat diet mice in parallel with Moringa oleifera leaves ethanol extract (MOLE). Forty … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…Human clinical researches also observed that male patients with ulcerative colitis had weight loss while the female patients do not suffer from weight loss, [25,26].Bábíèková et al [23] also reported progressive loss of body weight in male mice compared with the female mice. Just like the effect recorded in this study, the female mice in the study by Babiekova et al [27][28][29][30] recovered faster. The difference may have been accounted for by the effect of progesterone [30].…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Human clinical researches also observed that male patients with ulcerative colitis had weight loss while the female patients do not suffer from weight loss, [25,26].Bábíèková et al [23] also reported progressive loss of body weight in male mice compared with the female mice. Just like the effect recorded in this study, the female mice in the study by Babiekova et al [27][28][29][30] recovered faster. The difference may have been accounted for by the effect of progesterone [30].…”
Section: Discussionsupporting
confidence: 83%
“…The elevated level of red blood cells (RBC) was observed the younger female rat compared to the older while it was reduced in the younger male rats compared to the older rats. Decrease in the red blood parameters has been linked to anaemia caused by low grade inflammation [29].The reduction in younger rat compared to older adult is poorly understood but this may be due to higher metabolism rate of the younger rats [30]. There was no effect on PDW, PCT, Basophils, Eosinophils, platelet, MPV, MCV and WBC in this study.…”
Section: Groupsmentioning
confidence: 49%
See 1 more Smart Citation
“…EDTA prevents blood clotting by binding to calcium ions, crucial for the coagulation process, thereby inhibiting the coagulation cascade and maintaining the blood in a liquid, non-clotting state. 15,[20][21][22][23][24] The processed blood is then analyzed using the Mindray BC20s hematology analyzer, following the manufacturer's protocol.…”
Section: Measurement Of Blood Parametersmentioning
confidence: 99%
“…Furthermore, M. oleifera and isothiocyanate concentrates may decrease gene expression and the production of inflammatory markers in RAW macrophages. In particular, they attenuate the expression of inducible nitric oxide synthase (iNOS), IL-1β, and the production of NO and TNFα at 1 and 5μM.1 1,12 Further study indicate MOLE has the potential to reduce triglyceride levels, glucose levels 11,13,14 also increase hemoglobin levels, and reduce granulocyte presentation in mice models of chronic inflammation due to a high-fat diet 15 and diabetes. 11,13,14 However, there have been no studies related to MOLE in sepsis model mice.…”
Section: Introductionmentioning
confidence: 99%